Assessment of the infectivity of corneal buttons taken from hepatitis B surface antigen seropositive donors. Issue 1 (January 1995) - Khalil, A; Ayoub, M; el-Din Abdel-Wahab, K S; el-Salakawy, A
Abstract : Sixty one corneas taken from 33 hepatitis B surface antigen (HBsAg) seropositive donors and 20 control corneas taken from 12 HBsAg seronegative donors were tested for the presence of HBsAg using reversed passive haemagglutination (RPHA) and enzyme linked immunosorbent assay (ELISA) and for the presence of hepatitis B virus core DNA (HBVcDNA) using the hybridisation technique in their epithelium, stroma endothelium, and storage media. HBsAg was detected by ELISA in the epithelium of one cornea (1.6%), in the stroma endothelial suspensions of six corneas (9.8%), and in the storage media of five corneas (8.2%). HBVcDNA was detected for the first time in the cornea; in the epithelium of four corneas (6.6%), stroma endothelium of nine corneas (14.8%), and the storage media of five corneas (8.2%). The control corneas were negative for HBsAg, while HBVcDNA was detected in the stroma endothelium of two corneas (10%) and in the media of two corneas (10%). This study confirmed that HBV can be present in the human cornea. Preservation in corneal storage media for up to 6 days could not eliminate the virus from the cornea. The possibility of HBV transmission through corneal transplantation should not be overlooked.